Coding task performance in early adolescence: a large-scale controlled study into boy-girl differences - Dekker, Sanne; Krabbendam, Lydia; Aben, Aukje; De Groot, Renate H.; Jolles, Jelle (Frontiers in Psychology, 2013)
This study examined differences between boys and girls regarding efficiency of information processing in early adolescence. 306 healthy adolescents (50.3% boys) in grade 7 and 9 (aged 13 and 15 respectively) performed a coding task based on over-learned symbols. An age effect was revealed as subjects in grade 9 performed better than subjects in grade 7. Main effects for sex were found in the advantage of girls. The 25% best-performing students comprised twice as many girls as boys. The opposite pattern was found for the worst performing 25%. In addition, a main effect was found for educational track in favor of the highest track. No interaction effects were found. School grades did not explain additional variance in LDST performance. This indicates that cognitive performance is relatively independent from school performance. Student characteristics like age, sex and education level were more important for efficiency of information processing than school performance. The findings imply that after age 13, efficiency of information processing is still developing and that girls outperform boys in this respect. The findings provide new information on the mechanisms underlying boy-girl differences in scholastic performance.